Leadership and positive human functioning: a triphasic proposal - Gomes, António Rui (2014)
This chapter addresses the topic of leadership by proposing the Triphasic Model of Leadership Efficacy. The model explains leadership efficacy by suggesting that the best results achieved by the leaders result from a congruent hypothesis that congregates a conceptual cycle of leadership (that includes the elements of leadership philosophy, leadership practice, and leadership criteria) and a practical cycle of leadership (that includes the elements of leadership philosophy, leadership in practice, and leadership criteria). The model also reinforces the importance of considering the antecedent factors of leadership (e.g., situational, leader, and members’ characteristics) as possible mediators of the leadership process (which includes the conceptual and practical cycles). The advantages of using the triphasic process of action instead of a tripartite process of leadership that use erratic and non-linear forms of relationships between the leadership philosophy, the leadership in practice, and the leadership criteria are also discussed. Finally, the chapter presents possibilities of testing the triphasic model and discusses implications to the training of leaders according this proposal.